Dysregulation and imbalance of innate and adaptive immunity are involved in the cardiomyopathy progression - He, Bin; Quan, Li-Ping; Cai, Chun-Yu; Yu, Dian-You; Yan, Wei; Wei, Qin-Jiang; Zhang, Zhen; Huang, Xian-Nan; Liu, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiomyopathy is known to be a heterogeneous disease with numerous etiologies. They all have varying degrees and types of myocardial pathological changes, resulting in impaired contractility, ventricle relaxation, and heart failure. The purpose of this study was to determine the pathogenesis, immune-related pathways and important biomarkers engaged in the progression of cardiomyopathy from various etiologies.Methods: We downloaded the gene microarray data from the GEO. The hub genes were identified using differential expression analysis,LASSO regression and WGCNA. To assess the diagnostic precision of hub genes, ROC curves were utilized. Then,KEGG enrichment pathway analysis and GO analysis were conducted on the obtained differential genes. Finally, GSEA and ssGSEA were utilized to analyze the infiltration level of 28 immune cells and their relationship with hub genes .Results: A total of 82 DEGs were screened . The WGCNA analysis clustered the expression profile data into four co-expression modules, The turquoise module exhibited the strongest relationship with clinical traits, and nine candidate key genes were obtained from the module. Then we intersected DEGs with nine candidate genes. LASSO regression analysis identified the last three hub genes as promising biomarkers. ROC curve analysis revealed the sensitivity and accuracy of three hub genes as marker genes. The majority of the functional enrichment analysis results were concentrated on immunological and inflammatory pathways. Immune infiltration analysis revealed a significant correlation between regulatory T cells, type I helper T cells, macrophages, myeloid-derived suppressor cells, natural killer cells, activated dendritic cells and the abundance of immune infiltration in hub genes.Conclusion: The hub genes (CD14, CCL2, and SERPINA3) can be used as markers to distinguish cardiomyopathy from non-cardiomyopathy individuals. Among them, SERPINA3 has the best diagnostic performance. T cell immunity (adaptive immune response) is closely linked to cardiomyopathy progression. Hub genes may protect the myocardium from injury through myeloid-derived suppressor cells, regulatory T cells, helper T cells, monocytes/macrophages, natural killer cells and activated dendritic cells. The innate immune response is crucial to this process. Dysregulation and imbalance of innate immune cells or activation of adaptive immune responses are involved in cardiomyopathy disease progression in patients.